Maternal Cardiac and Obstetric Performance in Consecutive Pregnancies in Women With Heart Disease. Issue 3 (September 2016) - Gelson, E.; Curry, R.; Gatzoulis, M.A.; Swan, L.; Lupton, M.; Steer, P.J.; Johnson, M.R.
Abstract : ( BJOG. 2015;122(11):1552–1559) Pregnant women with preexisting cardiac disease often experience cardiac decompensation due to the physiological stresses of pregnancy. Some studies have suggested that these adverse effects on cardiac function might not be reversible once the pregnancy is completed. Therefore, women with cardiac disease might be expected to experience increased complications and poorer outcomes with subsequent pregnancies. This current study was undertaken to determine the effect of a second pregnancy on cardiac, obstetric, and perinatal complications in women with heart disease, compared with the first pregnancy in the same women. It secondarily estimated the effect of a second pregnancy on birth weight in women with heart disease.